Substances Affecting the Central Nervous System (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Antidepressants, caffeine group, camphor group, strychnine group drugs, respiratory center in veterinary medicine, stimulants, various plant and animal world, the importance of stimulants.